A produção social e política dos homicídios: uma análise macrossocial da trajetória das taxas de homicídios em Santa Catarina (1992 a 2017) - Monteiro, Felipe Mattos (2019)
In recent decades, homicide rates tended to increase in Santa Catarina. Between 1992 and 2017 the rates increased from 8.0 to 17.0 deaths per thousand inhabitants, which means an increase of 112.5%. A series of studies have been investigating both upward and downward trends of homicide in different contexts. However, the majority of them focus their analysis on general trends, which in turn disregards the existence of latent heterogeneity. Therefore, this thesis aims at investigating the homicide rate trajectory in cities of Santa Catarina (1992 to 2017) in order to answer three central questions: 1) in a state characterized by both important regional differences and homicide rate increase, could there be a hidden heterogeneity in homicide rates? In other words, the increasing trend in Santa Catarina state could hide different trajectories with distinct characteristics and specificities? 2) Would it be possible to identify a typology of homicide trends over time related to increase, stability or decrease? 3) What is more, once such typology is registered, would it be possible to establish the grounds for such distinction, i.e., what would determine that a set of cities is settled in a certain group of high trajectory compared to the low trajectory? To identify the existence of latent trajectory as well as groups of cities with similar trajectories over time, a Group-Based Trajectory Modeling has been used. After this work, we developed an index series, which shows the main arguments found in macrosociological studies about homicides. By means of a binary and multinomial logistic regression study, we established the grounds of the typological distinction, i.e., we point out which situational, structural and political aspects can explain the inclusion of a city in a certain trajectory group. To solve the problem of overestimated homicide rates in small-sized towns where the risk of homicide is smaller, their homicide numbers were transformed into local empirical Bayesian rates. Data were collected at two main sources: information available at the Mortality Information System (SIM/Datasus) and at the Public Security Bureau in Santa Catarina. Our results show that there is an underlying structure in the main homicide rate trend in Santa Catarina. Four latent trajectories with heterogeneous trends between 1992 and 2017 were identified: intense increase, moderate increase, decrease and stability. Regarding the mapping of distinct typologies, i.e., the reasons why a city belongs to a certain trajectory group, we observed a complex relationship, which combines the effects of structural aspects, actions of crime control and situational issues according to each trajectory characteristic.